1997
DOI: 10.3147/jsfp.32.51
|View full text |Cite
|
Sign up to set email alerts
|

Mass Mortalities in the Production of Juvenile Greasyback Shrimp, Metapenaeus ensis, Caused by Penaeid Acute Viremia(PAV).

Abstract: Very high mortalities of juvenile Metapenaeus ensis occurred in the seedling production at public sea-farming centers in west Japan during 1994 and 1995. Moribund shrimp exhibited no apparent external signs except small obscure white spots on the body, and were proved to be free from any causative bacteria, fungi and parasites. Infection trials reproduced the disease in both healthy juvenile M. ensis and Penaeus japonicus. The disease was characterized by nuclear hypertrophy of the necrotic cells in various or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The tissues of ecto-mesodermal origin, i.e., the cuticular epithelia, gills, lymphoid organ, hematopoietic tissue, myocardium, hemocytes and various connective tissues have been reported as targets of the virus. Viral propagation within the nucleus leads to nucleus enlargement and is recognized as pathognomonic indicating the viral infection Momoyama et al, 1994;Takahashi et al, 1994;Momoyama et al, 1995;Lo et al, 1997;Momoyama et al, 1997;Lightner et al 1998;Momoyama et al, 1999;Rajendran et al, 1999;Wang et al, 1999;Pantoja and Lightner, 2003;Rodriguez et al, 2003;Yoganandhan et al, 2003). Despite these many histopathological studies of PAV and WSD, we determined the histopathological features in the previous reports showed little tissue damages and not severe enough to cause mortality.…”
Section: Necrosis Penaeus Japonicusmentioning
confidence: 88%
“…The tissues of ecto-mesodermal origin, i.e., the cuticular epithelia, gills, lymphoid organ, hematopoietic tissue, myocardium, hemocytes and various connective tissues have been reported as targets of the virus. Viral propagation within the nucleus leads to nucleus enlargement and is recognized as pathognomonic indicating the viral infection Momoyama et al, 1994;Takahashi et al, 1994;Momoyama et al, 1995;Lo et al, 1997;Momoyama et al, 1997;Lightner et al 1998;Momoyama et al, 1999;Rajendran et al, 1999;Wang et al, 1999;Pantoja and Lightner, 2003;Rodriguez et al, 2003;Yoganandhan et al, 2003). Despite these many histopathological studies of PAV and WSD, we determined the histopathological features in the previous reports showed little tissue damages and not severe enough to cause mortality.…”
Section: Necrosis Penaeus Japonicusmentioning
confidence: 88%
“…However, extremely severe hypoxia presumably affects survival, and thus the number of cohorts. Detailed research is required on the relationship between survival-growth of M. ensis and hypoxia and other environmental factors, such as temperature (Abe et al 1995, Park & Loneragan 1999, diet, predation (Primavera 1997) and disease (Momoyama et al 1997). …”
Section: Sakuramoto 2013)mentioning
confidence: 99%
“…Penaeid acute viremia (PAV) causes serious problems for kuruma shrimp farmers Takahashi et al, 1994Takahashi et al, , 1996 and was also reported in the seedling production of greasyback shrimp (Metapenaeus ensis) in Japan (Momoyama et al, 1997). The caus ative agent of PAV is the penaeid rod-shaped DNA virus (PRDV, formerly named RV-PJ).…”
Section: Introductionmentioning
confidence: 99%